Pulmonary Tumour Embolism Complicating a Case of Leiomyosarcoma. (1998) - Gentle, Stephen; Fisher, Cyril; Soni, Neil; Hill, Sue; Thomas, J. Meirion
Abstract : Patient. A case of peripheral leiomyosarcoma presenting with features of pulmonary thromboembolism is described. Discussion. Persistence of the embolus despite triple-armed thrombolytic therapy and the presence of intravascular tumour invasion suggest the rare entity of pulmonary tumour embolism from a leiomyosarcoma.